2019
DOI: 10.15829/1560-4071-2019-1-32-37
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arterial hypertension, smoking, and their combination on mortality (according to the results of a 27-year cohort prospective study of the unorganized population of Tomsk)

Abstract: Aim. To study the influence of arterial hypertension (AH), smoking, and their combination on the risk of all cause and cardiovascular mortality.Material and methods. We conducted a 27-year cohort prospective study of the unorganized population of Tomsk (916 women and 630 men aged 20-59 years). At the first stage, we studied the prevalence of AH and smoking (1998-1991), at the second (2015) — the effect of these risk factors (RF) and their combination on the risk of all cause and cardiovascular mortality. AH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
3
0
10
Order By: Relevance
“…Thus, in the Russian cohort study of residents of Tomsk I.V. Dolgalev et al showed that the risk of dying in persons with hypertension is 2.2 times higher than in persons without this disease [2]. It is known that the level of blood pressure (BP) per se plays an important prognostic role.…”
Section: Prevalence Of Hypertension In Russian Federation распространmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the Russian cohort study of residents of Tomsk I.V. Dolgalev et al showed that the risk of dying in persons with hypertension is 2.2 times higher than in persons without this disease [2]. It is known that the level of blood pressure (BP) per se plays an important prognostic role.…”
Section: Prevalence Of Hypertension In Russian Federation распространmentioning
confidence: 99%
“…Долгалев и соавт. показали, что риск умереть у лиц с АГ в 2,2 раза выше в сравнении с лицами, не имеющими этого заболевания [2]. Известно, что и уровень артериального давления (АД) per se играет важную прогностическую роль.…”
Section: Prevalence Of Hypertension In Russian Federation распространunclassified
“…A negative relationship between BMI and smoking has been confirmed in many studies; (15,16) nevertheless, it has been shown that smoking is an independent risk factor for the development of cardiovascular diseases, including stroke and coronary heart disease. (12,(24)(25)(26) Table 1 presents a comparative analysis of overweight and obesity in the general population, depending on gender and on the status of smoking. The frequency of overweight in the general population of smokers was higher than in nonsmokers due to the higher rate of obesity among female smokers; however, the differences are statistically insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…При этом, если у мужчин чаще наблюдалось курение, то у женщин чаще регистрировался высокий уровень холестерина и ожирение [14]. Согласно данным 27-летнего исследования, проведенного в Томске, сочетание курения и повышенного АД приво-Primary Prevention of CVD Первичная профилактика ССЗ дит к увеличению относительного риска общей и сердечно-сосудистой смертности в 5 раз [15]. В 2019 г. эксперты American College of Cardiology (ACC) представили упрощенную версию рекомендаций AHA, названных в виде аббревиатуры "ABCDE", отражающих первые буквы ведущих факторов риска ССЗ [16].…”
Section: шкалы для стратификации риска ссзunclassified
“…Кроме того, результаты 27-летнего исследования, проведенного в Томске с участием 1546 человек, показали, что ОР общей смертности у обследуемых лиц с АГ увеличивается в 2,2 раза, в то время как при сочетании с курением -в 5,2 раза. При этом у пациентов, бросивших курить, отмечался риск смерти от ССЗ в 1,8 раз выше по сравнению с некурящими [28].…”
Section: курениеunclassified